The cost of poverty alleviation transfer programs: a comparative analysis of three programs in Latin America - Caldés, Natàlia; Coady, David; Maluccio, John A. (International Food Policy Research Institute, 2004)
A common criticism of antipoverty programs is that the high share of administrative (nontransfer) costs substantially reduces their effectiveness in alleviating poverty. Yet there is surprisingly little hard empirical evidence on such programs' costs. A recent international review of targeted poverty alleviation programs in less developed countries found cost information -- which was rarely comparable between studies -- for fewer than one-third of the programs examined. Improved information and a better understanding of the costs of such programs are crucial for effective policymaking. This study proposes and implements a methodology for a comparative analysis of the level and structure of costs of three similar poverty alleviation programs in Latin America, in order to assess their cost-efficiency. The findings underscore that any credible assessment of cost-efficiency requires a detailed analysis of program cost structures that goes well beyond simply providing aggregate cost information. -- Authors' Abstract